Birth weight associations with DNA methylation differences in an adult population. Issue 7 (3rd July 2021) - Madden, Rebecca A.; McCartney, Daniel L.; Walker, Rosie M.; Hillary, Robert F.; Bermingham, Mairead L.; Rawlik, Konrad; Morris, Stewart W.; Campbell, Archie; Porteous, David J.; Deary, Ian J.; Evans, Kathryn L.; Hafferty, Jonathan; et al.
ABSTRACT: The Developmental Origins of Health and Disease (DOHaD) theory predicts that prenatal and early life events shape adult health outcomes. Birth weight is a useful indicator of the foetal experience and has been associated with multiple adult health outcomes. DNA methylation (DNAm) is one plausible mechanism behind the relationship of birth weight to adult health. Through data linkage between Generation Scotland and historic Scottish birth cohorts, and birth records held through the NHS Information and Statistics Division, a sample of 1, 757 individuals with available birth weight and DNAm data was derived. Epigenome-wide association studies (EWAS) were performed in two independently generated DNAm subgroups (nSet1  = 1, 395, nSet2  = 362), relating adult DNAm from whole blood to birth weight. Meta-analysis yielded one genome-wide significant CpG site (p = 5.97x10 −9 ), cg00966482. There was minimal evidence for attenuation of the effect sizes for the lead loci upon adjustment for numerous potential confounder variables (body mass index, educational attainment, and socioeconomic status). Associations between birth weight and epigenetic measures of biological age were also assessed. Associations between lower birth weight and higher Grim Age acceleration (p(FDR)  = 3.6x10 −3 ) and shorter DNAm-derived telomere length (p(FDR)  = 1.7x10 −3 ) are described, although results for three other epigenetic clocks were null. Our results provide support for an association between birth weight and DNAm both locally at one CpG site, and globally via biological ageing estimates.